2013
DOI: 10.1371/journal.pone.0060712
|View full text |Cite
|
Sign up to set email alerts
|

Recent Geological Events and Intrinsic Behavior Influence the Population Genetic Structure of the Chiru and Tibetan Gazelle on the Tibetan Plateau

Abstract: The extent to which a species responds to environmental changes is mediated not only by extrinsic processes such as time and space, but also by species-specific ecology. The Qinghai-Tibetan Plateau uplifted approximately 3000 m and experienced at least four major glaciations during the Pleistocene epoch in the Quaternary Period. Consequently, the area experienced concurrent changes in geomorphological structure and climate. Two species, the Tibetan antelope (Pantholops hodgsonii, chiru) and Tibetan gazelle (Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 79 publications
8
14
1
Order By: Relevance
“…Three haplotype units without spatial clustering were detected based on a phylogeographic analysis of mtDNA sequences. These findings are in agreement with those of previously reported studies (Ruan et al 2005;Zhang et al 2013). However, we found no trait determining the habitat, host and other choices in favor of sympatric divergence among P. hodgsonii populations (Johannesson 2001).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Three haplotype units without spatial clustering were detected based on a phylogeographic analysis of mtDNA sequences. These findings are in agreement with those of previously reported studies (Ruan et al 2005;Zhang et al 2013). However, we found no trait determining the habitat, host and other choices in favor of sympatric divergence among P. hodgsonii populations (Johannesson 2001).…”
Section: Discussionsupporting
confidence: 94%
“…However, accumulating evidence on P. hodgsonii has suggested that the genetic differentiation among the geographically isolated populations is limited, despite high levels of genetic diversity (Ruan et al 2005;Zhou et al 2007;Du et al 2016). These findings differed from those for other native ungulate populations in the QTP Zhang et al 2013). The calving migration behavior exhibited by P. hodgsonii populations has been suggested to promote genetic exchange between different geographical populations, resulting in the homogenization of the genetic pool (Schaller et al 2005;Du et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…()* of STR loci was 0.7767 and 0.8446 for the within and among-deme studies respectively. Our results are consistent with previous studies (Du et al, 2016;F. Zhang, Jiang, Xu, Zeng, & Li, 2013).…”
Section: Tibetan Antelope Maintained High Genetic Diversity After a Hsupporting
confidence: 94%
“…The Mantel test detected no IBD pattern with neither mtDNA CR nor STR loci. This finding suggests historically wide gene flow, which is consistent with results of previous studies (F. Zhang et al, 2013;H. Zhou et al, 2007).…”
Section: No Obvious Population Structure Was Detected Among Three Geosupporting
confidence: 92%
“…Although the significance of the HTO for the evolution and biogeography of the Tibetan biota and those of adjacent regions is unquestioned, the influence of the geomorphological transformations, the corresponding glacial oscillations, and of the complex local topography on the distribution and diversification patterns of Tibetan species remains poorly understood (Yang et al, 2009;Qiu et al, 2011;Wang et al, 2011;Zhang et al, 2013). The lack of consensus on the chronology of the uplift (Spicer et al, 2003) and on the extent, timing and impact of Tibetan Plateau glaciations (Fu et al, 2013) as well as differences between taxa in evolutionary trajectories and responses to the same historical events (Yang et al, 2009)all contribute to this knowledge gap.…”
Section: Introductionmentioning
confidence: 99%